Dinamika Kurikulum Nasional: Tinjauan Sejarah dan Prospek Masa Depan - Imran, Imran (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This article discusses the history and recent developments of Indonesia's national curriculum, while also considering its future direction. Since independence, the national curriculum has undergone significant transformations, reflecting the evolution of education and responses to changing times. The historical journey of the curriculum includes periods of nationalist identity, technical focus during the industrial era, and inclusivity with emphasis on 21st-century skills. Recent developments show integration of technology and a focus on multidimensional competencies. The future of the curriculum faces global challenges and the fourth industrial revolution, necessitating adaptability, AI integration, and the development of soft skills. This article provides insights into the dynamics of Indonesia's national curriculum towards relevant and adaptive education in the modern era.